The Influence of Learning Discipline on the Learning Achievement of 'Ulya Class Students at the Raudhatut Thalibin Putri Islamic Boarding School - Muslimah, Naila; Nuruddaroini, M. Ahim Sulthan; Khalidi, Ahmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Learning discipline is often considered an important factor influencing academic achievement, particularly in Islamic boarding school environments where discipline is intensively cultivated. This research aims to assess the level of learning discipline among female students of the Ulya class (senior high school level) as well as their achievement in Arabic learning at Pondok Raudhatut Thalibin Putri, and to explore how the two variables are related. This study applies a quantitative correlational approach involving 50 female students selected by means of purposive sampling. The data were obtained through a learning discipline questionnaire and documentation of Arabic learning achievement scores. In analyzing the data, the study employed validity and reliability tests, descriptive statistics, normality and linearity examinations, along with simple regression analysis. The study reveals that learning discipline is categorized as high, while Arabic learning achievement is categorized as very high. However, regression analysis indicates that learning discipline does not significantly influence Arabic learning achievement (Sig = 0.241; R² = 0.028). This study suggests that, in the context of Islamic boarding schools, discipline is no longer a distinguishing factor in academic achievement, and other factors need further investigation.